2001
DOI: 10.1046/j.1365-8711.2001.04436.x
|View full text |Cite
|
Sign up to set email alerts
|

A survey of hard spectrum ROSAT sources - II. Optical identification of hard sources

Abstract: We have surveyed 188 ROSAT Position Sensitive Proportional Counter (PSPC) fields for X‐ray sources with hard spectra (α<0.5); such sources must be major contributors to the X‐ray background at faint fluxes. In this paper we present optical identifications for 62 of these sources: 28 active galactic nuclei (AGN) which show broad lines in their optical spectra (BLAGN), 13 narrow emission line galaxies (NELGs), five galaxies with no visible emission lines, eight clusters and eight Galactic stars. The BLAGN, NELGs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 34 publications
3
44
2
Order By: Relevance
“…No object with N H > 10 22 cm À2 shows broad lines in its optical spectrum. Nevertheless, 9% (8/86) of the BL AGNs in our sample do show some intrinsic absorption in their X-ray spectra (see also Mittaz et al 1999;Fiore et al 2001;Page et al 2001;Schartel et al 1997;Tozzi et al 2001;Mainieri et al 2002;Brusa et al 2003;Perola et al 2004;Mateos et al 2005b). In Figure 10 we show the distributions of the RÀK ( Vega) colors for the sources with PL as best-fit model (open histogram) and for the ones that instead require an absorbed power law (hatched histogram).…”
Section: Spectral Properties Of the Samplementioning
confidence: 59%
“…No object with N H > 10 22 cm À2 shows broad lines in its optical spectrum. Nevertheless, 9% (8/86) of the BL AGNs in our sample do show some intrinsic absorption in their X-ray spectra (see also Mittaz et al 1999;Fiore et al 2001;Page et al 2001;Schartel et al 1997;Tozzi et al 2001;Mainieri et al 2002;Brusa et al 2003;Perola et al 2004;Mateos et al 2005b). In Figure 10 we show the distributions of the RÀK ( Vega) colors for the sources with PL as best-fit model (open histogram) and for the ones that instead require an absorbed power law (hatched histogram).…”
Section: Spectral Properties Of the Samplementioning
confidence: 59%
“…In addition, we have selected all the HLIRGs (six) from the Stevens et al (2005) sample of high redshift X-ray Compton-thin absorbed QSO. These sources have been observed in X-rays by ROSAT (Page et al 2001) and by XMM-Newton (Page et al 2007), and by SCUBA in the sub-mm band (Page et al 2004). Table 2 presents the most relevant information about the XMM-Newton observations.…”
Section: The Hlirg Samplementioning
confidence: 96%
“…Therefore the increasing hardness of the source spectra at fainter fluxes observed in the Chandra deep fields (Giacconi et al 2001;Tozzi et al 2001;Brandt et al 2001) is probably due to intrinsic absorption and not to an intrinsically hard power law. Several teams (Della Ceca et al 1999b;Akiyama et al 2000;Fiore et al 2001;Maiolino et al 2001a;Page et al 2001;Reeves et al 2000;Risaliti et al 2001) reported the existence of AGN optically classified as Type-1 but with an indication of absorption in their X-ray spectra. In our sample, there are seven objects with an intrinsic absorption between 10 21 and 10 22 cm −2 which are optically classified as Type-1 AGN.…”
Section: Spectral Parametersmentioning
confidence: 99%